Congregational dhikr after salat an Islamic jurisprudential analysis - Jamaludin, Khairul Fahmi; Zakaria, Mohamad Sabri; Abdullah, Mohamad Asmadi; Abas, Afridah (Serials Publication (P) LTD, 2020)
The coming of Islam to Tanah Melayu has introduced various religious practices and rituals to Muslim community based on Shafi’e madhab. These religious practices have been modified and amalgamated with the customs of Malay community in Malaysia. Among them is the practice of congregational dhikr after daily prayer in which Muslim community in Malaysia have been accustomed with for generations. In recent decades, a group called the Salafi doctrine which is known for their call to return to Quran, sunnah and the practice of Salaf al- Salih has disputed various religious practices in Malaysia which includes congregational dhikr. As the disputes and objection by the Salafi doctrine has caused quarrel and fight among Muslim, various fatwa institutions in Malaysia have issued official fatwa on this practice for the purpose of maintaining unity and harmony within the Muslim community in Malaysia. This paper aims to study the methodology of ijtihad employed by four madhab and Salafi doctrine in deriving hukm (ruling) from Quran and Sunnah of the Prophet Muhammad (s.a.w.) as well as other sources of Islamic law in order to understand the reason for their disagreements and how to handle this disagreement properly. The paper adopts library research that will analyse of various Islamic law sources and writing of classical jurist of four (4) madhab. This paper reveals that four madhabs uses various rules of interpretation and relying on various sources of Islamic law in ijtihad process. While Salafi doctrine, on the other hand, focuses on using literal understanding and only relied on Quran and Sunnah of the Prophet Muhammad (s.a.w.) as well as the concept of al-Tark (Omission) in the rule-making process. It is hoped that this paper will give a better understanding on the reason for the differences in the methodology of ijtihad between these two groups that can help to preserve and maintain the unity and harmony within Muslim community in Malaysia.